Hemp seeds attenuate loperamide-induced constipation in mice - Hua, Huang; Yongtong, Wang; Xufeng, Ding; Fang, Li; Jing, Gu; Fumao, Zeng; Jie, Jiang; Lijiang, Ji (Frontiers in Microbiology, 2024)
Constipation is a common gastrointestinal disease that seriously affects human physical and mental health. Studies have reported that hemp seeds can improve constipation, however the specific mechanism is still unclear. This study investigates that hemp seed (HS) and its waterethanol extract (HSE) attenuates loperamide-induced constipation in mice. The research resultsshow that: the fecal water content and small intestinal transit rate of mice in the hemp seed group and hemp seed hydroalcoholic extract group were significantly increased compared with MC group, and the first red feces defecation time was significantly shortened; HS and HSE significantly influence serum levels of Gastrin (Gas), motilin (MTL), substance P (SP), and endothelin (ET), potentially mediating their effects on gastrointestinal motility. HS and HSE can improve colon inflammation in constipated mice with H&E staining. Compared with the model of constipation group, the content of short-chain fatty acids in the HS group and HSE group increased significantly.Gut microbiome studies have shown that the structure and abundance of intestinal flora are altered.HS and HSE changed the abundance of Odoribacter, Bacteroide, Lactobacillus and Prevotella.Together, these results suggest that HS have the potential to stimulate the proliferation of beneficial gut microbes and promote intestinal motility, thereby improving gut health and relieving symptoms of constipation.